Adjuvant therapy with carboplatin and pamidronate for canine appendicular osteosarcoma2. (10th May 2013) - Kozicki, A. R.; Robat, C.; Chun, R.; Kurzman, I. D.
Abstract Amputation and chemotherapy are the mainstay of treatment for canine appendicular osteosarcoma (OSA). In vitro studies have demonstrated anti‐tumour activity of pamidronate against canine OSA. The purpose of this study was to assess the safety of adding pamidronate to standard post‐operative carboplatin chemotherapy in 17 dogs with appendicular OSA treated with limb amputation. Median disease‐free interval (DFI) and median survival time (MST) were evaluated as secondary endpoints. Incidence of side effects and treatment outcomes were compared to 14 contemporary control patients treated with carboplatin alone. There were no identified side effects to the pamidronate treatment. The median DFI for the study group was 185 days compared to 172 days for the control group (P = 0.90). The MST of the study group was 311 days compared to 294 days for the control group (P = 0.89). Addition of pamidronate to carboplatin chemotherapy for the treatment of canine appendicular OSA is safe and does not impair efficacy of standard carboplatin treatment.